а) 5√3 +3√5 или √75 +7√2 ; (5√3 +3√5) -(√75 +7√2) = (5√3 +3√5) -(√25*3 +7√2)=(5√3 +3√5) -(5√3 +7√2) =5√3 +3√5 -5√3 -7√2 =3√5 -7√2 =√(3²*5) -√(7²*2) =√45 -√98 <0⇒ 5√3 +3√5 <√ 75 +7√2 . б) √112 -2√5 или 4√7 -√23 ; (√112 -2√5) - (4√7 -√23 ) =(√(16*7) -2√5) - (4√7 -√23 ) =4√7 -2√5 -4√7 +√23 =√23 -2√5 =√23 -√(2²*5) =√23 -√20 > 0⇒√112 -2√5 > 4√7 -√23 .**************************************************************************а
) 5√3 +3√5 или √75 +7√2 ; 5√3 +3√5 или √25*3 +7√2 ; 5√3 +3√5 или 5√3 +7√2 ; 5√3 +3√5 или 5√3 +7√2 ;3√5 или 7√2 ;√(3²*5) или √(7²*2) ;√45 < √98 ;